Implementation of the Oversight Function of the Aceh Special Autonomy Fund - zulkifli, Muchlis; Hafidz, Jawade (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2023)
This study aims to identify and analyze the mechanism for implementing the oversight function of the Aceh Special Autonomy Fund (DOKA) of the Aceh People's Representative Council on the Government of Aceh and to determine and analyze the impact of oversight of the Aceh Special Autonomy Fund (DOKA) of the Aceh People's Representative Council on the Government of Aceh. The research method used is sociological juridical with statutory approach, conceptual approach and sociological approach based on descriptive analytical research specifications. Based on the results of the study it was concluded that First; The Regional People's Legislative Council is a Regional People's Representative Body and is domiciled as an element of regional government administration which has a supervisory function, namely carrying out supervision of the implementation of Regional Regulations and other Laws and Regulations, Regional Head regulations, APBD, regional government policies in implementing regional development programs, and international cooperation in the regions with the aim of such supervision is a form of preventive action against handling various deviations that endanger and detrimental to the rights and interests of the region, society and the state. Second; that in order to guarantee the implementation of a good government (good governance) supervision must be carried out by the Aceh People's Legislative Council as the implementation of the functions of the said institution. Supervision is a form of every effort and action in order to find out the extent to which tasks are carried out according to the provisions and targets to be achieved. The ultimate goal of supervision is to achieve results in accordance with a predetermined plan. Oversight from the Aceh People's Legislative Assembly which starts from discussing the budget to submitting accountability reports from the Government of Aceh (Governor) is not very effective considering that these two institutions have many interests in them.